Fezes de galinhas poedeiras na alimentação de ruminantes análises microbiológicas - Schockeniturrino, R. P.; Defreitas, JCM; Sampaio, AAM; Sampaio, MAPM (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1992)
The objectives of the present study were: to evaluate the variation in total number of microorganisms in laying hen fecal samples and to identify the pathogenic microorganisms possibly present such as Staphylococcus aureus, Salmonella sp., Clostridium botulinum, C chauvoei, Campylobacter sp., Escherichia coli, and Corynebacterium sp. The experiment was conducted at the School of Agrarian and Veterinarian Sciences of Jaboticabal, - UNESP. Fecal samples were collected from the aviary. A fully randomized experimental design was used with 7 treatments and 4 replications, for a total of 28 samples. A decrease in total number of microorganisms was detected when treatment T0 (zero days of storage) was compared with treatment T6 (42 days of storage), with oscillations in numbers being observed during this period of time. Pathogenic bacteria such as Clostridium noyvi, C perfringens, C sordelli, C septicum and C noyvi type B were detected, as well as non-pathogenic bacteria such as Bacillus sp. and Staphylococcus epidermidis.

Os objetivos deste trabalho foram: avaliar a variação do número total de microrganismos em amostras de fezes de galinhas poedeiras e identificar os microrganismos patogênicos possivelmente presentes, tais como: Staphylococcus aureus, Salmonella sp., Clostridium botulinum, C. perfringens, C. chauvoei Campylobacter sp., Escherichia coli e Corynebacterium sp. O experimento foi conduzido na Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal, UNESP, onde foram coletadas amostras de fezes procedentes do aviário. O delineamento experimental foi inteiramente casualizado, com 7 tratamentos e 4 repetições, totalizando 28 amostras. A avaliação demonstrou que houve decréscimo no número total de microrganismos quando se comparou T0 (zero dias de estocagem) com o tratamento T6 (42 dias), havendo, no intervalo, oscilações neste número. Constatou-se a presença de bactérias patogênicas nas amostras de fezes, tais como: Clostridium noyvi, C. perfringens, C sordelli, C. septictun, C noyvi tipo B, havendo a presença de outras bactérias não patogênicas como Bacillus sp., Staphylococcus epidermidis.
Laying hen feces for ruminant feeds microbiological analyses
Keywords: Microorganisms; Storage